Development of Nursing Education in Line with Technological Developments in Health Care - Leila Valizadeh; Hossein Nemati (Future of Medical Education Journal)
Today, one of the major challenges of nursing education and practice is the demand for technological developments in health care. Undoubtedly, the management of technology in the health system requires training proficient human resources with knowledge and skills in the field of technology. Due to developments in new technologies and the application of such technologies in the field of health care, especially in nursing care, it is necessary to prepare nurses to effectively use these tools to improve health. Given the increasing need for electronic learning, it is necessary to develop electronic learning systems with appropriate technology. Some new technologies include virtual reality stimulation (VR), augmented reality (AR), Metaverse, blockchain technology, the Internet of Things (IoT), and artificial intelligence, which are used to provide opportunities to transfer information, improve learning, and reduce learning problems. Technology-based care can play a key role in developing remote nursing services. Since studies have indicated that there will be an increased shortage of nurses in the coming years, designing and implementing educational plans for nurses has been considered an effective and useful approach in this regard, which can improve nursing consequences in dealing with technological developments, and improve working interactions between health and treatment personnel, and increase the quality of care if effectively planned.